Achieving sustainable, environmentally viable, solarized vaccine cold chain system and vaccination program—an effort to move towards clean and green energy-driven primary healthcare in Lebanon - Kapuria, Bhrigu; Sami Hamadeh, Randa; Mazloum, Farah; Korbane, Joe Akl; Aung, Kyaw; Kamal, Doaa; Chamoun, Nariman; Syed, Sabin (Frontiers in Health Services, 2024)
Introduction Lebanon faces severe economic and energy crises, impacting its healthcare system, particularly vaccine storage. Traditional gas or kerosene-powered refrigerators often fail to maintain necessary temperatures for vaccine efficacy. This study explores transitioning to solar direct-drive (SDD) refrigerators to ensure reliable vaccine storage. Methods A multi-phase methodology was employed, beginning with an inventory assessment of existing cold chain equipment. The implementation involved stepwise replacement of identified refrigerators across health facilities, including Primary Health Care Centers (PHCCs) and dispensaries. Feasibility, cost-effectiveness, and environmental impact were evaluated. Results Findings indicate that solarization significantly reduces vaccine wastage, ensures stable temperatures, and cuts operational costs by decreasing dependence on non-renewable energy sources. Over 1,000 SDD units were installed across more than 800 health facilities. Additionally, PHCC solarization improved vaccine preservation and enhanced the resilience of health services overall. Discussion The solarization initiative demonstrates the critical role of renewable energy in strengthening healthcare infrastructure, especially in crisis-hit regions. Solar-powered systems provide a reliable and sustainable solution for vaccine storage, reduce carbon footprints, and build public trust in the immunization system. Challenges included geographical and structural limitations, which were addressed through comprehensive planning and collaboration with local stakeholders. Solarization of Lebanon's vaccine cold chain and PHCCs marks a significant step towards sustainable and resilient healthcare infrastructure. The model offers a robust framework for other regions facing similar economic and energy challenges, highlighting the importance of renewable energy solutions in healthcare.